Arching in Piled Embankments Including the Effects of Reinforcement and Subsoil - Zhuang, Yan (Springer Nature, 2025)
This Open access book examined the performance of the reinforced piled embankments in both plane strain and three-dimensional conditions. The arching mechanisms involved in the piled embankments have been investigated by conducting a series of ﬁnite element analyses. A better understanding of the variation for the performance of the piled embankments along with the change of the embankment geometry and piles arrangement has been achieved. This book also considered predictions of reinforcement tension in a piled embankment from British standard BS 8006 published in 2010 and the 2012 amended version, and compared the results with finite-element model predictions. Good predictions of maximum reinforcement sag are achieved by slight modiﬁcation of the BS 8006 method. Furthermore, the book considered the potentially beneficial contribution of a lightly overconsolidated clay subsoil layer, both in the finite-element predictions and as a simple modification to the BS 8006 predictive method. When compared to the finite-element results the proposed modified BS 8006 prediction is quite accurate. Finally, the concept of an interaction diagram and corresponding equation for use in design is proposed, which considered the effect of soil arching, the contribution of reinforcement and the subsoil. The calculation of the vertical stress carried by the subsoil due to arching effect and reinforcement for multilayered soil was proposed. The results show that subsoil gives a major contribution to overall vertical equilibrium, while the reinforcement gives obvious contribution at relatively large settlement. Good design practice is necessary to prevent excessive settlement of piled embankments. This book can enhance the understanding of the load transfer mechanism in piled embankments. The research results will provide a scientific basis and technical support for the settlement control of embankments for the design life of the infrastructure in soft soil areas.